20th Congress of the European Burns Association (EBA) - Nadia Depetris; Alette De Jong; Clemens Schiestl; Franck Duteille; Jill Meirte; Joan P. Barret-Nerin; Paul Van Zuijlen; Jyrki Vuola; Stian Almeland (European Burn Journal, 2023)
Abstracts of the plenary and special interest sessions, workshops, and oral and poster presentations of the 20th EBA Congress in Nantes, France from 6–9 September 2023.